Electrical and electronic equipment waste as a secondary source of critical and strategic materials - Marcelo Pilotto Cenci; Priscila Silva Silveira Camargo; Felipe Antônio Lucca Sánchez; Andréa Moura Bernardes; Hugo Marcelo Veit (Ambiente & Sociedade)
Abstract Brazil has recently released a list of prioritized strategic materials addressing issues related to trade balance, supply, and technology development. In this context, it is possible to associate waste electrical and electronic equipment (WEEE) as an important secondary source for several types of materials. The composition of these wastes is extremely complex and includes many materials from the Brazilian list. The objective of this study is to characterize some types of WEEE to assess the presence and quantities of these materials, thus promoting their recycling. High concentrations of strategic materials such as Al, Cu, Ni, Li, Co, Si, Au, and rare earth elements have been identified in printed circuit boards, batteries, LEDs, and solar panels. It can be inferred that WEEE is an important source of raw materials, and the consolidation of a national recycling system is essential to promote a circular economy and national sovereignty.